The response of cultural policies in COVID-19 pandemic: The case of Slovakia - Miriam Šebová; Zuzana Révészová; Barbora Andor Tóthová (Scientific Papers of the University of Pardubice, Series D: Faculty of Economics and Administration, 2021)
Culture can be a powerful driver for development, with broad social, economic and environmental impacts. UNESCO acknowledged the role of culture as an enabler and a driver of sustainable development. There are undisputable effects of culture on community building, social cohesion and empowering people. The economic importance of the cultural sector is growing. Creative and cultural industries can be a source of structural economic development, job creation and innovation. The sector of culture is among the hardest hit by the corona crisis in the whole of Europe. In Slovakia, the sector suffered by austerity measures also before the pandemic. The paper is focused on the impacts of a COVID 19 pandemic on the cultural and creative sector in Slovakia. The paper's objective is to critically analyse the supportive measures for the sector at the national and local level. The theoretical framework is based on the cultural policy and its evolution in Slovakia, which created the baseline for the analysis. The paper summarises local and national bodies' compensations for cultural workers and organisations based on text analysis of available documents. There is also presented a case study of a local cultural centre in Košice. The data for the case study stems from the semi-structured interviews with the managers of the centre about the impacts of a pandemic on their business. The results show that the policies to support firms and workers during the pandemic can be scarcely adapted to the non-traditional business models and employment forms in the cultural sector.
Keywords: P25; Z18; 330; Pandemic; Cultural And Creative Industries; Cultural Policy